A new monoraphid diatom species from the genus Karayevia sensu lato (Bacillariophyceae: Stauroneidaceae) with remarks on taxonomy and phylogeny of the genus. Issue 1 (2nd January 2022) - Tseplik, Natalia; Glushchenko, Anton; Maltsev, Yevhen; Kuznetsova, Irina; Genkal, Sergei; Kociolek, John Patrick; Kulikovskiy, Maxim
Abstract : A new monoraphid diatom, Karayevia chelonica sp. nov., is described from Nha Trang, Vietnam, isolated from marine littoral habitats. Phylogenetic analysis based on partial 18S rDNA and rbc L sequences places this species within the family Stauroneidaceae, and related to other monoraphid species. Karayevia chelonica sp. nov. differs from other species in the genus in stria density and a broad axial area on the rapheless valve. Morphology and taxonomy of the closely related genera Karayevia, Kolbesia and Madinithidium are discussed. Based on morphological characteristics, we conclude that these three genera might represent a single genus, however, further molecular investigation is required to clarify their taxonomic and systematic affinities.